2005
DOI: 10.1177/000348940511400404
|View full text |Cite
|
Sign up to set email alerts
|

Protective Glottic Closure: Biomechanical Effects of Selective Laryngeal Denervation

Abstract: Glottic closure constitutes the primary mechanism for prevention of intradeglutitive and postdeglutitive aspiration. Laryngeal paralysis therefore exerts a considerable impact on deglutition, yet little is understood regarding the biomechanical effects of selective denervation on the laryngeal protective function. We measured the glottic closing force (GCF) in each of 6 male, 40-kg Yorkshire pigs 1) after selective unilateral superior laryngeal nerve (SLN) section; 2) after selective unilateral recurrent laryn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…non-lapping). Several other investigators use the infant pig as a model for studying swallowing problems [2327]. …”
Section: Introductionmentioning
confidence: 99%
“…non-lapping). Several other investigators use the infant pig as a model for studying swallowing problems [2327]. …”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that bilateral SLN lesions result in a significantly high incidence of aspiration [5, 6] and that unilateral sensory loss of the laryngopharynx can cause aspiration as well [7]. Sasaki et al [8] reported that a unilateral SLN lesion results in reduced force of glottic closure in the pig, and they implied that this could contribute to laryngeal aspiration. Using a different style of experiment, Amis et al [9, 10] reported that stimulation of the external SLN (eSLN) in dogs activates the cricothyroid muscle and causes both pharyngeal dilation and glottis constriction.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, would the authors alternatively consider the strength of glottic closure rather than cordal apposition alone to determine the effectiveness of laryngeal protection? The data in this regard appear as plausible for dysphagia arising by the loss of motor function as one might attribute to the loss of localized sensory function [2]. We do not doubt that voice and swallow therapy are helpful.…”
Section: Commentmentioning
confidence: 71%